2023
DOI: 10.1212/wnl.0000000000207831
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Detection of Large Vessel Occlusion Stroke With EEG

Maritta N. van Stigt,
Eva A. Groenendijk,
Laura C.C. van Meenen
et al.

Abstract: Background and objectivesEndovascular thrombectomy (EVT) is standard treatment for anterior large vessel occlusion stroke (LVO-a stroke). Prehospital diagnosis of LVO-a stroke would reduce time-to-EVT by allowing direct transportation to an EVT-capable hospital. We aim to evaluate the diagnostic accuracy of dry electrode electroencephalography (EEG) for detection of LVO-a stroke in the prehospital setting.MethodsELECTRA-STROKE was an investigator-initiated, prospective, multi-center, diagnostic study, performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The ELECTRA-STROKE study 8 has enhanced our understanding of the feasibility and potential clinical utility of dry electrode EEG as a prehospital triage tool for identifying LVO in the anterior circulation in patients with suspected stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ELECTRA-STROKE study 8 has enhanced our understanding of the feasibility and potential clinical utility of dry electrode EEG as a prehospital triage tool for identifying LVO in the anterior circulation in patients with suspected stroke.…”
Section: Discussionmentioning
confidence: 99%
“…ELECTRA-STROKE is a prospective, multicenter, nonrandomized, single-arm diagnostic Dutch study with blinded outcome assessment. 8-11 It is based on the concept that EEG is good in depicting neuronal changes caused by brain ischemia. 12 Previous studies have identified EEG patterns in stroke patients, emphasizing an increase in slow waves (theta, delta) and a decrease in fast waves (alpha, beta).…”
Section: Hypothesis and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these are attractive options due to their inherent portability, low-cost, and potential discriminatory ability to differentiate stroke syndromes. One study demonstrated an EEG cap during ambulance transportation can accurately differentiate LVO stroke, reporting a diagnostic accuracy of 91% and a positive likelihood ratio of 11.0 ( 41 ). Another study investigating a portable, automated TCD device and found the overall accuracy of LVO detection was 91% when combining two biomarkers.…”
Section: Future State: Artificial Intelligence To Enhance Prehospital...mentioning
confidence: 99%
“…16,17 Transcranial Doppler, volumetric impedance phase shift spectroscopy (VIPS), and electroencephalography (EEG) have been studied to this end with varying degrees of diagnostic accuracy. 1821 Lastly, in addition to performance metrics, it is important to consider cost, size, efficiency, and ease of use in the pre-hospital setting. 22…”
Section: Introductionmentioning
confidence: 99%